IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA LAPORAN KEUANGAN KOPERASI SERBA USAHA ”AKEN MITRA SEJATI” CAKRANEGARA - UTAMI, LUH; FITRI, SYARIFAH MASSUKI; SAPUTRA, ZULFIKRI SATRIAWAN (Universitas Mahasaraswati K. Mataram, 2023)
Cooperatives as economic entities make financial reports as a means of accountability to members and cooperative management. Cooperative financial reporting is regulated in the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). Considering that the need to prepare and present financial reports guided by SAK ETAP greatly influences the continuity of cooperative businesses, therefore this research aims to analyze the extent of implementation of SAK ETAP in the preparation and presentation of financial reports of KSU